Legal culture of religious capitalism: Socio legal approach on employment relations between muslimah employers and batik workers in pekalongan - Shinta Dewi Rismawati (Proceedings of AICS - Social Sciences, 2013)
Pekalongan called as world's city of batik and religious city. The business of batik controlled by the women entrepreneurs. They are a good Muslim. But not in legal culture of the behaviors are of their business. Especially at the relationship with their workers. It doesn’t reflect its identity as a good Muslim. They are ignoring Islamic values and regulation about worker (Act number 13 in 2004. In fact, the legal culture of the behavior of business is based on the values of capitalism. The behavior of the mended with the assumption of a new identity as a religious capitalist. They make accumulation their profit by exploited their labors. For example, always recruited inexperienced new workers so their paid with low wages; equating the standard wage for all workers, whether experienced or not; utilize resignation workers; majority of workers are women so the wages are lower; determine the wage unilaterally; rewardby way of installments, the restinstalled payment paid with the checks/demand deposits with maturities of retreat between 2 to 3 months and; doesn’t provide health insurance, welfare and rights of the workers leave, or give them with a very low standard. Representation of religious identity as a Muslim, there is the level of new religious rituals not only in the identity business behavior.Keywords : Legal Culture, Relationship, Religious, Capitalist